In light of all darkness : inside the Polly Klaas kidnapping and the search for America's child - Cross, Kim (Kimberly Hisako), 1976- (Grand Central Publishing, 2023)
"Paced like a thriller and full of insider information on the history and science of Crime Scene Investigation, In Light of All Darkness embeds readers in one of the most famous true-crime stories of our generation-the kidnapping of Polly Klaas-a case as pivotal in the history of the FBI as the Unabomber or Oklahoma City bombing. On October 1, 1993, a 12-year-old girl was kidnapped at knifepoint from her bedroom in Petaluma, California, during a sleepover with two friends, while her mother slept soundly in the room next door. This rarest of all kidnappings-a stranger abduction from the home-triggered one of the largest manhunts in FBI history. Riddled with red herrings, grave mistakes, dead ends, and false leads, from fake ransom calls to junior high pranks to dramatic SWAT raids, the 65-day search for "America's Child" became every FBI agent's-and every parent's-worst nightmare. Many Americans remember Polly's face, which appeared on the national news every night, on the cover of People magazine, and on more than 8 million flyers distributed as far as China. The emotional gravity of Polly's story touched every agent, police officer, and forensic technician who worked on her case. Many of these investigators have never shared their stories-until now. New York Times bestselling author Kim Cross has written the first comprehensive account of what happened on that fateful night in October, as well as how the case forever transformed the Bureau's approach to solving crimes. With unprecedented access to files, crime scene photos, a videotaped murder confession, and inside sources, In Light of All Darkness follows the investigators who pieced together the evidence that led to the arrest and conviction of the kidnapper-a man currently on death row-and made the victim a household name and a girl who will never be forgotten. The book will be published on the 30th anniversary of Polly's disappearance"--